Penggunaan Finansial Teknologi Aplikasi Mobile BMT NU Balen untuk Peningkatan Anggota dan Pendapatan (Studi pada BMT NU Balen di Bojonegoro) - Alfi, Tutik Al-Fiyah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2024)
This study evaluates the effectiveness of digital technology implementation on BMT NU Balen's mobile application in increasing the number of customers and revenue located in Balen sub-district, Bojonegoro Regency. Digitalization at BMT NU Balen has improved operational efficiency by reducing administrative costs and manual transactions. This study used a qualitative method with a case study approach, involving observation, interviews, and documentation as data collection techniques. Data before and after the implementation of the mobile application was analyzed to measure its direct impact. The results showed that the financial technology implemented in BMT NU Balen's mobile application successfully increased the number of customers from 570 in 2020 to 4,150 in 2023, which means an increase of 3,580 members or seven times. BMT NU Balen's revenue also increased significantly from 251 million rupiah in 2020 to 1.716 billion rupiah in 2023, which means an increase of 1.465 billion rupiah or five to six times. The results of this study are expected to provide valuable insights for BMT NU Balen and other microfinance institutions in utilizing technology to increase the number of customers and revenue, as well as support the development of a more efficient microfinance ecosystem.